Mucin histochemistry by paradoxical concanavalin A staining in early gastric carcinomas. - Cho, K. J. (Korean Academy of Medical Sciences, 1991)
Phenotypic expression of tumor cells was investigated in 33 early gastric carcinomas by mucin histochemistry using paradoxical concanavalin A staining. This staining method had been developed to differentiate 3 classes of mucins located at various sites of the alimentary tract. Twenty-five (76%) tumors contained mixtures of neutral or acid class II mucin and class III mucin, suggesting the origin of multipotential stem cells. The surface mucous cell expression was more dominant than the pyloric gland or intestinal phenotypes in the well-and poorly differentiated adenocarcinomas. The intestinal properties of the tumor cells were noted not only in the well-differentiated but also in the poorly differentiated or signet ring cell carcinomas, not closely being related to the presence of background intestinal metaplasia. Signet ring cell carcinomas revealed a distinct pattern of mucin histochemistry compared with the other types.